PROCESS SIMULATION OF CRUDE OIL STABILIZATION SYSTEM : AN INDUSTRIAL CASE SUDY - DAINURE, MUHAMMAD FIRDAUS (Universiti Teknologi PETRONAS, 2013)
Petroleum is a naturally occurring flammable liquid of complex hydrocarbons found in oil reservoir beneath the Earth's surface. Crude oil (live crude) are sent to oil refineries for it to be processed into marketable petroleum products. However, before being transported to the refineries, the crude oil need to be stabilized beforehand since it contains light components that could flash off in low pressure conditions. This paper aims to find the suitable operating conditions to stabilize an incoming live crude feed to maximum True Vapor Pressure (TVPs) of 10 psia and 12 psia at Terengganu Crude Oil Terminal, TCOT. A simulations of the process has been conducted by using Aspen HYSYS (ver. 2007) software. It was found that at an heat exchanger outlet temperature of 85 - 90 ⁰C, High Pressure Separator, V-220 A/B and Low Pressure Separator, V-230 A/B operating pressure of (400 - 592 kPa) and (165 - 186 kPa) respectively. The effects of major parameters, i.e. inlet feed properties, three phase separators operating pressure and pre-heaters trains performance on the product TVP are also studied. Based on the scenarios analyzed, it can be concluded that actual water volume (kbbl/d) has greater impact on heat exchanger's duty, thus incoming free water to TCOT should be less than 19.5 kbbl/d (9.1 vol%).